RARE CASE WITH MEGALOBLASTIC ANAEMIA - Saleem, Munnaza; Shah, Syed Sajid Hussain; Mehmood, Tahir (Journal of Ayub Medical College Abbottabad, 2014)
A nine years old boy presented with history of pallor and anaemia since early infancy along with neural hearing loss responding to empirical multivitamin and folic acid therapy started on basis of blood complete picture showing anaemia and megaloblastic anaemia. On investigation he was diagnosed with Thiamine Responsive Megaloblastic Anaemia, a very rare condition in our settings. Keywords: Megaloblastic Anaemia, Thiamine Responsive Megaloblastic Anaemia, Thiamine, Sensorineural Hearing Loss